A Systematic Comparison between 1-D and 3-D Hemodynamics in Compliant Arterial Models - Xiao, Nan (Int J Numer Method Biomed Eng, 2013)
In this article, we present a systematic comparison of computational hemodynamics in arterial models with deformable vessel walls using a one-dimensional (1-D) and a three-dimensional (3-D) method. The simulations were performed using a series of idealized compliant arterial models representing the common carotid artery, thoracic aorta, aortic bifurcation, and full aorta from the arch to the iliac bifurcation. The formulations share identical outflow boundary conditions and have compatible material laws. We also present an iterative algorithm to select the parameters for the outflow boundary conditions using the 1-D theory to achieve a desired systolic and diastolic pressure at a particular vessel. This 1-D/3-D framework can be used to efficiently determine material and boundary condition parameters for 3-D subject-specific arterial models with deformable vessel walls. Finally, we explore the impact of different anatomical features and hemodynamic conditions on the numerical predictions. The results show good agreement between the two schemes, especially during the diastolic phase of the cycle.